2004
DOI: 10.1897/03-41
|View full text |Cite
|
Sign up to set email alerts
|

Sediments are major sinks of steroidal estrogens in two United Kingdom rivers

Abstract: The occurrence of intersex fish in a number of European rivers has been attributed to exposure to estrogenic chemicals present in sewage treatment work (STW) effluents. To further understand the environmental fate of these contaminants, the estrogenic activity of effluents, water, and sediments were investigated both upstream and downstream of the major STW discharge in two United Kingdom rivers. Estrogenic activity, determined using the yeast estrogen-receptor transcription screen, of the major STW effluents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
99
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(110 citation statements)
references
References 39 publications
9
99
2
Order By: Relevance
“…This is consistent with the general water quality classification of the three rivers. The estrogenic activities detected in surface water and sediment of the Shijing River were approximately one to two orders of magnitude higher than those reported in Korea [32], Portugal [33], the United Kingdom [34], and the United States [35], where the estrogenic activities ranged from below the limit of detection to 4.01 ng EEQ/L in surface water and from below the limit of detection to 12.1 ng EEQ/g in sediment. The estrogenic activities in the rivers of other regions clearly fall in the range for the Liuxi and Zhujiang rivers.…”
Section: Discussioncontrasting
confidence: 54%
“…This is consistent with the general water quality classification of the three rivers. The estrogenic activities detected in surface water and sediment of the Shijing River were approximately one to two orders of magnitude higher than those reported in Korea [32], Portugal [33], the United Kingdom [34], and the United States [35], where the estrogenic activities ranged from below the limit of detection to 4.01 ng EEQ/L in surface water and from below the limit of detection to 12.1 ng EEQ/g in sediment. The estrogenic activities in the rivers of other regions clearly fall in the range for the Liuxi and Zhujiang rivers.…”
Section: Discussioncontrasting
confidence: 54%
“…These values are comparable to YES E2 EQs reported by other studies, including sediments collected from the UK rivers with 0.20-13 ng E2 EQ g −1 dw (Thomas et al 2004) and German rivers with 0.03-1.3 ng E2 EQ g −1 dw (Grund et al 2011), as well as the values of sediment analysis from Dutch inland and estuarine waters ranging from 0.10 to 1.2 ng E2 EQ g −1 dw (Legler et al 2002) and from Chinese Liao River with non-detectable to 6.04 ng E2 EQ g −1 dw ). On the other hand, sediment YES-E2 EQs reported in our present study are much greater than those reported in other studies, including sediments from the UK estuaries with 0.021-0.03 ng E2 EQ g −1 SEQ (Peck et al 2004), from Dutch inland and estuarine waters with 0.005 and 0.34 ng E2 EQ g −1 SEQ (Houtman et al 2006), and sediment from a Korean lake with E2 EQs ranging from 0.003 to 0.064 ng E2 EQ g −1 dw (Koh and Khim 2005).…”
Section: Er Agonist Potencies Of Sediment Extractscontrasting
confidence: 89%
“…It is hypothesized that this distribution may relate with a sedimentation effect in the reservoir. Surface sediments are frequently a sink for persistent organic pollutants and EDCs in riverine environments (Ahlf et al 2002;Forstner and Westrich 2005;Labadie et al 2007;Vigano et al 2006;Peck et al 2004;Wang et al 2011). The sediment load in the Yangtze River is 500 Mt (1 Mt=1,000,000 t) year −1 (Zhang 1995).…”
Section: Profile Of Ahr and Er Activities In Tgr Sedimentsmentioning
confidence: 99%
“…Picogram to nanogram per liter concentrations of estrogenic activity have been found throughout the aquatic environment, e.g. in wastewater, surface water, and sediment (Jobling et al 1998;Belfroid et al 1999;Bolz et al 2001;de Alda and Barcelo 2001;Petrovic et al 2002;Houtman et al 2004b;Peck et al 2004;Cespedes et al 2005;Houtman et al 2006a;Morteani et al 2006). …”
Section: Endocrine Disrupting Compoundsmentioning
confidence: 99%